Modular genetic architecture underlies human hand and foot evolution - Alexander S. Okamoto; Gayani Senevirathne; Pushpanathan Muthuirulan; Campbell Rolian; Terence D. Capellini; Ian A. Glass; Kimberly A. Aldinger; Dan Doherty; Ian G. Phelps; Jennifer C. Dempsey; Mei Deng; Eric Y. So; et al. (Proceedings of the National Academy of Sciences, 2026)
The functional divergence of the hand and foot for prehension and locomotion, respectively, has long been recognized as a critical event in human evolution, and involved substantial changes to the skeleton. Hominins evolved a more muscular and opposable thumb while the other fingers are relatively shorter, enhancing manipulative capacity. The feet evolved robust first toes and short lateral toes to meet the challenges of bipedal walking and running. While adaptations in the hand and foot have often been considered separately, the fore- and hind limbs of primates are morphologically integrated, serially homologous structures, raising the possibility that natural selection on either autopod may have driven corresponding changes in the other. To explore the genetic architecture underlying human autopod evolution, we used functional genomics methods to identify regulatory elements and gene expression in the developing phalanges and metacarpals of the human hand and foot. We identified genetic modules based on patterns of gene expression or regulatory activity, which strongly distinguish the metapodials from the phalanges and separate tissues to a lesser extent along the anterior–posterior axis or between limb types. We show that some of these genetic modules are enriched for human-specific genomic features, which potentially underlie anatomical differences in the autopod skeleton between humans and other apes. We find stronger enrichments for human-specific genomic features related to the foot than the hand, consistent with models hypothesizing stronger selective pressure on the human foot during the transition to bipedalism. Our results highlight the modular genetic architecture underlying human autopod evolution.